Sacred then and sacred now : the return of the old Latin Mass - Woods, Thomas E.; Catholic Church. Pope (2005-2013 : Benedict XVI). (Fort Collins, CO : Roman Catholic Books, 2008)
An introduction to the traditional Latin Mass for priests and lay persons who want to know more about the "Extraordinary Form of the Mass" which is now an official part of the liturgy of the Catholic Church. The text is well documented with references to the ancient liturgy, to the Magisterium, to the current and recent popes. The old Mass has made a dramatic comeback and is the wave of the future. Ten years from now the worship of the Church will be close to what it was before the drastic innovations of 1970.
Includes the text of the motu proprio Summorum Pontificum in English translation (p. 97-103).
Keywords: Benedict -- XVI, -- Pope, -- 1927-; Catholic Church -- Liturgy -- History; Mass -- Celebration -- History -- 20th century; Lord's Supper -- Catholic Church